نموذج فاما وفرينش لاختبار العوامل الثلاث لأداء المحافظ التقليدية في بورصة ماليزيا. - ارحومة, د. هاني نوري (Dirasat in Economics and Business, 2021)
The main objective of this research is to test whether the style factors employed by the Fama and French (1993) three-factor model adequately explain the performance of the conventional sub-portfolios sorted by market values and their Shariah-compliant counterparts in Bursa Malaysia over the examination period from 1 December 2005 to 30 November 2017. The test was conducted by regressing the monthly excess returns of the conventional and Shariah sub-portfolios on the monthly returns of the Fama and French (1993) factors, which are the market risk premium, the small-cap risk premium, and the value risk premium. The results revealed that the Fama and French (1993) three-factor model can significantly explain the performance of the four conventional sub-portfolios sorted by market value and their Shariah-compliant counterparts.